A pedagogia da leitura: análise de material didático na perspectiva da educação linguística - Grammont, Ana Terra Reis de (2012)
Reading pedagogy: schoolbook analysis under the Linguistic Education perspective is the outcome of an investigation carried out from 2009 to 2012 following the Portuguese language reading, writing and teaching research track from the Portuguese Language Studies Program from the Pontific Catholic University of São Paulo, guided by Prof., Dr. Dieli Vesaro Palma, PUC-SP Linguistic Education for Portuguese Teaching research group leader PUC-SP GREDLINP-. The following research has intended to analyze it under the Linguistic Education perspective in what way the schoolbook explores the reading pedagogy so the following questions can be answered: 1. What is the reading model which rests under the schoolbook? 2. How do the authors try to awake the learners´ previous knowledge? So the analysis is done we have used the critic interpretative research, which lies in the research qualitative paradigm, aiming for analyzing the Portuguese Language schoolbook text interpreting and comprehension exercises of the Fundamental School II 6th grade from school collection Portuguese Languages, featuring William Roberto Cereja and Thereza Cochar Magalhães as authors. We conclude that the cognitive reading model awakened by the questions was interactive, although the majority is bottom-up, contrasting with the top-down (KLEIMAN, 2008 and KATO, 1990). The authors try to awake the readers-learners´ previous knowledge through the interpreting questions, besides saving a section in each unity for this purpose. Therefore, we consider achieving satisfactory our goal: 1. Discovering what reading model rests under the proposal of the analyzed LD. 2. Analyzing how the authors try to awake the learners´ previous knowledge